ABO blood group alleles and prostate cancer risk: Results from the breast and prostate cancer cohort consortium (BPC3). Issue 15 (13th August 2015) - Markt, Sarah C.; Shui, Irene M.; Unger, Robert H.; Urun, Yuksel; Berg, Christine D.; Black, Amanda; Brennan, Paul; Bueno‐de‐Mesquita, H. Bas; Gapstur, Susan M.; Giovannucci, Edward; Haiman, Christopher; Henderson, Brian; et al.
<x xml:space="preserve">Abstract</x> Background ABO blood group has been associated with risk of cancers of the pancreas, stomach, ovary, kidney, and skin, but has not been evaluated in relation to risk of aggressive prostate cancer. Methods We used three single nucleotide polymorphisms (SNPs) (rs8176746, rs505922, and rs8176704) to determine ABO genotype in 2, 774 aggressive prostate cancer cases and 4, 443 controls from the Breast and Prostate Cancer Cohort Consortium (BPC3). Unconditional logistic regression was used to calculate age and study‐adjusted odds ratios and 95% confidence intervals for the association between blood type, genotype, and risk of aggressive prostate cancer (Gleason score ≥8 or locally advanced/metastatic disease (stage T3/T4/N1/M1). Results We found no association between ABO blood type and risk of aggressive prostate cancer (Type A: OR = 0.97, 95%CI = 0.87–1.08; Type B: OR = 0.92, 95%CI =n0.77–1.09; Type AB: OR = 1.25, 95%CI = 0.98–1.59, compared to Type O, respectively). Similarly, there was no association between "dose" of A or B alleles and aggressive prostate cancer risk. Conclusions ABO blood type was not associated with risk of aggressive prostate cancer. Prostate 75:1677–1681, 2015. © 2015 Wiley Periodicals, Inc.